Penataan Kedudukan Dan Kewenangan Majelis Permusyawaratan Rakyat Republik Indonesia - Subanrio Subanrio; Arie Elcaputera (Universitas Bengkulu, 2021)
After the amendment, there was a rearrangement of the constitutional system building towards a more democratic one in accordance with the demands of reform. This occurs as a result of a shift in the Indonesian constitutional system, one of which is a shift in the paradigm of state institutions. Changes in the position of state institutions have consequences on their duties and authorities. This research is a normative legal research that uses a conceptual and statutory approach. This research discusses and analyzes the problems of structuring the position and authority of the People's Consultative Assembly of the Republic of Indonesia; the existence and position of the People's Consultative Assembly as a State institution equal to other state institutions; and Amendments to the Constitution as stipulated in Article 37 of the 1945 Constitution of the Republic of Indonesia. The urgency of structuring the position and authority of the People's Consultative Assembly is a problem in itself in responding to Indonesia's current constitutional challenges. The 1945 Constitution of the Republic of Indonesia after the amendment did not place the MPR as the highest state institution, but was equal or equal to other state institutions. The MPR is also no longer the full actor of people's sovereignty, and its authority is very limited, including in amending the constitution, but the limited powers of the MPR do not mean that constitutional amendments cannot be made. Keywords: Arrangement; Position; Authority. AbstrakPasca amandemen, terjadi penataan ulang terhadap bangunan sistem ketatanegaraan kearah yang lebih demokratis sesuai tuntutan reformasi. Hal ini terjadi akibat dari pergeseran sistem ketatanegaraan Indonesia, salah satunya pergeseran paradigma kelembagaan negara. Perubahan kedudukan lembaga-lembaga negara mempunyai konsekuensi pada tugas dan wewenang. Penelitian ini merupakan penelitian hukum normatif yang menggunakan pendekatan konseptual dan perundang-undangan. Penelitian ini membahas dan menganalisis permasalahan penataan kedudukan dan kewenangan Majelis Permusyawaratan Rakyat Republik Indonesia; keberadaan dan Kedudukan Majelis Permusyawaratan Rakyat sebagai lembaga Negara sejajar dengan lembaga negara lainnya; serta Perubahan Undang-Undang Dasar sebagaimana diatur dalam Pasal 37 Undang-Undang Dasar Negara Republik Indonesia tahun 1945. Urgensi penataan kedudukan dan kewenangan Majelis Permusyawaratan Rakyat menjadi sebuah problematika tersendiri dalam menjawab tantangan ketatanegaraan Indonesia saat ini. UUD NRI 1945 setelah amandemen tidak menempatkan MPR sebagai lembaga Negara tertinggi, tetapi sejajar atau sederajat dengan lembaga-lembaga negara lainnya. MPR juga bukan lagi sebagai pelaku penuh kedaulatan rakyat, dan kewenangannya sangat terbatas termasuk dalam mengubah undang-undang dasar namun dengan terbatasnya kewenangan MPR bukan berarti tidak bisa dilakukannya perubahan konstitusi. Kata Kunci: Penataan; Kedudukan; Kewenangan.